Rapid, ultrasensitive and highly specific diagnosis of Mycoplasma pneumoniae by a CRISPR-based detection platform - Zhou, Juan; Xiao, Fei; Fu, Jin; Jia, Nan; Huang, Xiaolan; Sun, Chunrong; Xu, Zheng; Zhang, Yu; Qu, Dong; Wang, Yi (Frontiers in Cellular and Infection Microbiology, 2023)
Mycoplasma pneumoniae (MP) is an important causative agent of morbidity and mortality among all age groups, especially among patients of extreme ages. Improved and readily available tests for accurate, sensitive and rapid diagnosis of MP infection is sorely needed. Here, we developed a CRISPR-Cas12b-based detection platform on the basis of recombinase polymerase amplification (RPA) for rapid, simple, and accurate diagnosis of MP infection, named MP-RPA-CRISPR. The RPA was employed for amplifying the community-acquired respiratory distress syndrome (CARDS) toxin gene of MP strains at the optimal reaction temperature 37°C. The resulting amplicons were decoded by the CRISPR-Cas12b-based detection platform, which was interpreted by real-time PCR system and by naked eye under blue light. The MP-RPA-CRISPR can detected down to 5 fg of genomic DNA templates of MP strains and accurately distinguish MP strains from non-MP strains without any cross-reactivity. A total of 96 bronchoalveolar lavage fluid (BALF）samples collected from patients suspected of respiratory infection were used to evaluate the clinical performance of the MP-RPA-CRISPR assay. As a result, our assay accurately diagnosed 45 MP-infected samples and 51 non-MP infected sample, and the results obtained from MP-RPA-CRISPR were consistent with microfluidic chip technology. In conclusion, our MP-RPA-CRISPR assay is a simple, rapid, portable and highly sensitive method to diagnose MP infection, which can be used as a promising tool in a variety of settings including clinical, field, and resource-limited aeras.